2013
DOI: 10.1016/j.jalz.2012.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Dementia severity and weight loss: A comparison across eight cohorts. The 10/66 study

Abstract: BackgroundWe aimed to investigate the association between dementia severity and weight loss in countries with low and middle incomes, where most prevalent cases reside.MethodsCross-sectional catchment area surveys were performed in Cuba, Mexico, Venezuela, Peru, Dominican Republic, Puerto Rico, China, and India. In 16,538 older adults (≥65 years of age), significant weight loss was self-reported and confirmed by an informant. We conducted neuropsychological testing and clinical and neurological assessments. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 37 publications
6
51
1
5
Order By: Relevance
“…Our result regarding weight loss being associated with increased dementia related mortality risk fits with studies using clinical dementia as end point (10)(11)(12)(13)(14)(15)(16)(17)(18). Most previous studies investigate weight change in old age, typically above 65 years or older, where reverse causality might be a plausible explanation for the association between weight loss and dementia.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our result regarding weight loss being associated with increased dementia related mortality risk fits with studies using clinical dementia as end point (10)(11)(12)(13)(14)(15)(16)(17)(18). Most previous studies investigate weight change in old age, typically above 65 years or older, where reverse causality might be a plausible explanation for the association between weight loss and dementia.…”
Section: Discussionsupporting
confidence: 85%
“…A better understanding of the association between body weight and dementia may be achieved by studying weight trajectories and patterns from midlife into old age (1). Studies with weight at multiple time points have generally reported weight loss (10)(11)(12)(13)(14)(15)(16)(17)(18) or weight instability (19) to be associated with increased dementia risk. However, many of these studies are limited to weight trajectories in old age, and might be prone to reverse causality because dementia and preclinical dementia might cause weight loss (1,20).…”
Section: Introductionmentioning
confidence: 99%
“…Weight loss is present in the initial stages of the disease, beginning even before diagnosis of the disease, and becoming more common with its progression. Evidence from the international 10/66 study confirms that the association between dementia and weight loss increases through the stages of dementia severity, and that geographical variations across diverse regions of the world are essentially negligible [18].…”
Section: Weight Lossmentioning
confidence: 91%
“…Regarding general nutritional status, a close relation between weight loss [18,43,54] as well as BMI [55,56] and disease severity is documented in older patients with dementia. There are also several prospective observational studies available which have demonstrated that weight loss [43,57,58] and malnutrition [59,60] are associated with disease progression and cognitive decline.…”
Section: The Role Of Nutrition In Disease Progressionmentioning
confidence: 99%
“…24,25 However certain studies have reported weight loss and not obesity as a predictor of incident dementia suggesting a possible protective role especially for late life obesity. 26,27 As obesity is widely prevalent in India and vascular dementia is the second most common types of dementia in clinical practice in India, we decided to investigate the phenomenon of obesity in Indian subjects with vascular dementia.…”
Section: Introductionmentioning
confidence: 99%